2001
DOI: 10.1128/jvi.75.14.6359-6366.2001
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Core Antigen Binds and Activates Naive Human B Cells In Vivo: Studies with a Human PBL-NOD/SCID Mouse Model

Abstract: The hepatitis B virus (HBV) core (HBc) antigen (HBcAg) is a highly immunogenic subviral particle. Studies with mice have shown that HBcAg can bind and activate B cells in a T-cell-independent fashion. By using a human peripheral blood leukocyte (hu-PBL)-Nod/LtSz-Prkdc scid /Prkdc scid (NOD/SCID) mouse model, we show here that HBcAg also activates human B cells in vivo in a T-cell-independent way. HBcAg was capable of inducing the secretion of HBcAg-binding human immunoglobulin M (IgM) in naive human B cells de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 24 publications
5
47
1
Order By: Relevance
“…Moreover, recent data indicate that HBcAg can also bind to and activate B cells via a linear motif present in the FR1-CDR1 junction of the heavy or light chain of the B cell surface receptor [26]. The latter process may also lead to the induction of co-stimulatory molecules required for efficient priming of Th cells [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, recent data indicate that HBcAg can also bind to and activate B cells via a linear motif present in the FR1-CDR1 junction of the heavy or light chain of the B cell surface receptor [26]. The latter process may also lead to the induction of co-stimulatory molecules required for efficient priming of Th cells [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HBcAg directly binds to and activates a large fraction of naive B cells [25], both murine and human, via linear conserved regions of the Ig heavy and light chains [26]. Finally, HBcAg expresses multiple Th epitopes for CD4 + T cells [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The capsid is composed of 180 or 240 copies of the 21 kDa core protein and exhibits hepatitis B virus core antigenicity (HBcAg). HBcAg is a unique immunogen and functions as both a T cell-independent and a T cell-dependent antigen in mice and humans (Cao et al, 2001;Milich & McLachlan, 1986). The immunogenicity of HBcAg has been proposed to rely on its structural properties (Fehr et al, 1998;Milich & McLachlan, 1986;Schodel et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The region on HBcAg involved in binding to sIg on naive B cells has not been mapped. HBcAg binds directly to a large proportion of naive human and mice B cells through this non-traditional antigen-antibody interaction (Cao et al, 2001;Lazdina et al, 2001a;Milich et al, 1997). The B cells become activated upon BCR cross-linking by HBcAg, as evidenced by an increase in the surface expression of B7-2 (Lazdina et al, 2001a;Milich et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It can therefore be presumed that the binding affinity of IgM anti-HBc changes depending on conformational changes of the epitope that may occur during the course of chronic hepatitis, culminating consequently in new antibody production. Cao et al [2001] developed an animal model similar to humans and showed that HBcAg directly activated B cells and induced IgM anti-HBc production in a T-cell independent fashion. Moreover, naïve B cells produced capsid-binding IgM, when co-cultured with very low levels of capsids and T-cells from HBcAg-specific T cell receptor transgenic mice .…”
Section: Discussionmentioning
confidence: 99%